Characteristics of Patients with Reproducible Masked Hypertension and its Diagnosis Approach - М. I. Smirnova; V. M. Gorbunov; Ya. N. Koshelyaevskaya; A. D. Deev; D. A. Volkov; N. V. Furman; P. V. Dolotovskaya (Рациональная фармакотерапия в кардиологии, 2020)
Background. Early diagnostics of masked hypertension (MH) is one of the key problems in modern cardiology due to the association of this blood pressure (BP) phenotype with doubled cardiovascular risk in comparison with normotension (NT). The current hypertension guidelines list numerous conditions, when the ambulatory BP monitoring (ABPM) is desirable in patients with normal office BP. However this list does not represent clearly defined, agreed and approved indications for ABPM as a diagnostic tool for MH.Aim. To develop a method of MH diagnostics for the use in routine clinical practice based on the comparing characteristics of patients with reproducible MH vs NT.Material and methods. The patients were selected from two trials that used ABPM (n=1778). The selection criteria included age 40-79 years, office BP<140/90 mm Hg, the absence of “hypertension” diagnosis or antihypertensive drug intake, and available results of two examinations (winter and summer): standard questionnaire, information about family history, chronic diseases and drug intake, height, weight, office and orthostatic BP and ABPM. We used the following definition of MH: elevated ambulatory BP (24-hour ≥130 and/or 80 mm Hg, daytime ≥135 and/or 85 mm Hg, or nighttime ≥120 and 70 mmHg) registered at both visits.Results. In total, 153 patients with reproducible (both winter and summer) BP phenotype were included: 127 with MH, and 26 with NT (mean age 49.1Ѓ}7.8 years, 36.1% males). In multivariate analysis, reproducible MH was associated with body mass index (β2.097; p<0.0001), office diastolic BP (β2.152; p<0.0001), orthostatic systolic BP (β1.031; p<0.023) and orthostatic heart rate (β0.773; p=0.19). These parameters were used in the original “MH coefficient” formula.Conclusions. MH is often found in patients with normal and optimal office BP and without “hypertension” diagnosis. The method described in the article helps to detect MH with high probability and define the individual indications for ABPM. The MH phenomenon in the category of patients warrants further investigation.